RECONCEPTUALIZING IJAB AND QABUL IN THE DIGITAL ERA: RETHINKING ISLAMIC CONTRACT FORMATION BEYOND PHYSICAL PRESENCE - Munawar Rizki Jailani; Danial; Ousmane Salifou Abdou; Iskandar (J-ISCAN: Journal of Islamic Accounting Research, 2026)
The rapid expansion of digital technologies has fundamentally reshaped the modes of interaction and exchange in contemporary economic transactions, raising critical questions regarding the validity and adaptability of classical Islamic contract principles. This study aims to reconceptualize the doctrines of ijab (offer) and qabul (acceptance) within the framework of the digital era by examining their transformation across electronic and virtual environments. Employing a qualitative and normative-juridical approach, this research integrates classical fiqh literature with contemporary regulatory frameworks and digital transaction practices, including e-commerce platforms, financial technology (fintech), and smart contracts. The findings reveal that while the essential elements of ijab and qabul -namely mutual consent (tarāḍī), clarity of expression, and temporal continuity-remain intact, their modes of articulation have undergone significant transformation. Digital interfaces, automated systems, and asynchronous communication challenge traditional assumptions of immediacy (ittisāl) and physical presence (majlis al-‘aqd), necessitating a broader interpretive approach grounded in maqāṣid al-sharī‘ah (objectives of Islamic law). The study argues that digital expressions -such as clicks, digital signatures, and algorithmic confirmations -can be recognized as valid manifestations of contractual consent, provided that they fulfill the principles of transparency, certainty, and the absence of coercion or ambiguity (gharar). This research contributes to the theoretical development of Islamic contract law by proposing a transformative framework that bridges classical jurisprudence and digital realities. It further offers practical implications for regulators, Islamic financial institutions, and digital platform developers in ensuring Shariah-compliant contract formation in an increasingly digitized economy. Ultimately, the study affirms that the principles of ijab and qabul are not static, but dynamically adaptable to technological evolution without compromising their normative essence.